The Influence of Students' Interest in Learning on Learning Achievement in Class XI Students' Trigonometry Material - Wahyudi, Ari; Pradipta Annurwanda (Program Studi Tadris Matematika Universitas Islam Negeri (UIN) Salatiga, 2024)
Education plays a crucial role in nation-building by significantly contributing to intellectual development, societal well-being, and the formation of national identity. Although SMA Negeri 1 Ngabang is known as a quality school, most students in grade XI MIPA face challenges in achieving adequate academic performance, especially in trigonometry. This research aims to determine the influence of students' learning interest on their performance in trigonometry at SMA Negeri 1 Ngabang. The research population includes all grade XI MIPA students at SMA Negeri 1 Ngabang, totaling 180 students, with samples consisting of classes MIPA B and MIPA D, totaling 72 students. This study is quantitative, using simple linear regression analysis as hypothesis testing. The results indicate that students' learning interest has a significant impact on their performance in trigonometry, with an influence level of 90.8%, while the remaining is influenced by other factors. Analysis of learning interest indicators shows that happiness contributes the most (48.4%), while attention contributes the least (34.6%). The conclusion of this research emphasizes the importance of enhancing students' learning interest to improve their academic performance.